Peculiarities of the electric resistivity behavior of R3(Ce,Nd,Sm)Cu4Sn4, R(Gd,Tb,Ho)NiSn2, DyNiSi, and DyNiSi3 compounds in magnetic fields - Kuzhel, B.; Salamakha, L.; Romaka, L.; Belan, B.; Dzevenko, M.; Gladyshevskii, R. (Physics and Chemistry of Solid State, 2022)
The resistance of ternary intermetallic compounds, namely RE(Ce, Nd, Sm)3Cu4Sn4 (space group Immm), RE(Gd, Tb, Ho)NiSn2 and DyNiSi (space group Pnma) and DyNiSi3 (space group Cmmm), has been studied in the temperature range up to 0.3 K and magnetic field up to 12 Tl. The temperature dependencies of electrical resistivity evidently show the anomalies at low temperatures. The anomalies of resistance temperature dependencies observed at the absence of an external magnetic field, agree well with magnetic phase transitions. In the majority of the investigated compounds, an increase of the external magnetic field leads to an erosion of the peculiarities on the temperature dependency of resistivity, right up to complete disappearance. Such effect is caused by the corresponding magnetic order phase transitions. Magnetic field influence on the temperature dependency of resistance is treated as an influence on the magnitude of hybridization between (s-d) conductivity electrons and localized f-electrons including influence on change on the charge caries mobility due to a possible spin-compensated interaction. Electron transport properties expose peculiarities in dependency of different chemical environment vicinity in elementary cell of crystal lattice and of magnetic state of the compound.